Data supporting: 'Ground Vibration Testing of a Flexible Wing: A Benchmark and Case Study' - Dessena, Gabriele (Cranfield University, 2023)
This CORD entry contains the experimental data underlying the journal article Ground Vibration Testing of a Flexible Wing: A Benchmark and Case Study published in Aerospace by MDPI. The document XB-2_Dataset.pdf serves as the explanatory note for the data contained in data_xb2.mat
Keywords: modal analysis'; 'experimental modal analysis'; 'flexible wing'; 'ground vibration testing'; 'beam'; 'vibration testing'; 'shaker testing'; 'dynamic testing'; 'high aspect ratio'; 'nonlinear dynamics'; 'Structural Engineering'; 'Aerospace Structures'; 'Aerospace Engineering'